EXERCISE WITH BAD FAITH OF SUBJECTIVE CIVIL RIGHTS - NICOLAE GRADINARU (Challenges of the Knowledge Society)
The abuse of rights is qualified as civil offence and it may not be different from that of aquilian responsibility, the purpose of its sanction is to protect the victim and not to punish the author. In the Romanian legal doctrine, the abuse of rights was defined as “the exercise of a civil subjective right by breaching the principles of its exercise.” The Constitutional Court held that the person exercising in bad faith and abusively his/her subjective or procedural rights is punishable by appropriate penalties, such as: dismissal of his/her legal action, obligation to bear the costs, application of certain court fines, etc.